Le dispositif dynamique à 3 pôles comme processus de professionnalisation : l’exemple d’un Groupe de Rencontres du Travail - Jean-Luc Denny; Brigitte Pagnani; Louis Durrive (Questions Vives)
The article deals with the link between activity analysis, work, and professionalization by cross-assessment-interpretation. It clarifies a process by which the use of a framework for analyzing professional practices, the Group of Work Meetings, can cause transformation among practitioners by entering an activity based on the ergological approach. It documents the existence of a matrix, the three poles dynamic device, inclined to potentialize any type of formal model for analyzing practices. The data relate to the activity of three teachers in a work situation of leading student debates. The methodology is based on simple and crossed self-confrontation. The results testify to the identification of a professionality obstacle which is followed by new ways of doing and thinking about the gestures of the work. A reflection on continuing education in France targeting socially sensitive issues is outlined.